Neuropsychological Tests of Memory, Visuospatial, and Language Function in Parkinson's Disease: Review, Critique, and Recommendations - Bezdicek, Ondrej; Biundo, Roberta; Boelema, Sarai; Cammisuli, Davide Maria; Cholerton, Brenna; Cronin-Golomb, Alice; Dalrymple-Alford, John C; Duits, Annelien; Fellows, Robert; Gerstenecker, Adam; El Hachioui, Hanane; Horáková, Hana; et al. (Movement disorders, 2025)
BACKGROUND: Cognitive impairment in Parkinson's disease (PD) is a key non-motor complication during the disease course. OBJECTIVES: A review of detailed cognitive instruments to detect mild cognitive impairment (PD-MCI) or dementia (PDD) is needed to establish optimal tests that facilitate diagnostic accuracy. METHODS: We performed a systematic literature review of tests that assess memory, language including premorbid intelligence, and visuospatial domains (for tests of attention and executive functions see accompanying review) to determine suitability to assess cognition in PD. Based on in-depth scrutiny of psychometric and other relevant clinimetric properties, tests were rated as "recommended," "recommended with caveats," "suggested," or "listed" by the International Parkinson and Movement Disorder Society (IPMDS) panel of experts according to the IPMDS Clinical Outcome Assessment Scientific Evaluation Committee guidelines. RESULTS: We included 39 tests encompassing 48 outcome measures. Seven tests (different versions or subtests of the test counted once) were recommended, including four for memory, one for visuospatial domains, one for language (including three measures), and one for estimated premorbid intelligence. Furthermore, 10 tests (12 measures) were "recommended with caveats," 11 were "suggested," and 11 (15 measures) were "listed." CONCLUSIONS: Recommended neuropsychological tests in memory, visuospatial functions, and language are proposed to guide the assessment of cognitive impairment and its progression in PD-MCI and PDD, and for use in clinical trials to stratify participants or as outcome measures. Novel measures being developed will need extensive validation research to be "recommended." © 2025 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.
Keywords: clinimetric; neuropsychology; rating scales; kognitivní dysfunkce; jazyk (prostředek komunikace); dementia; Parkinson's disease; cognitive; Cognitive Dysfunction; Neuropsychological Tests; lidé; test; Humans; Memory; paměť; neuropsychologické testy; Language; Parkinson Disease; Parkinsonova nemoc